THE RELATIONSHIP BETWEEN CHILD OBESITY AND BONE HEALTH - Cholidah, Rifana (Faculty of Medicine Universitas Mataram, 2013)
Since early childhood obesity has increased dramatically in the recent year, many researchers observe the relationship of excess fat mass during childhood and many health consequences including with bone health. This review aims to examine the relationship between childhood obesity and bone health. The results are conflicting. Several results show that fat mass have a strong positive relationship with increase bone mass and bone area, while other studies found obesity may increase the risk of fracture and may be detrimental on bone health. By these findings, further studies should be conducted to examine the effect of childhood obesity and bone health, also to evaluate the mechanisms how excess fat mass may increase or reduce bone growth.